(untitled) (Historia, 2021)
I do not own a copy of Colin Rae's Malaboch. Of course I do have a Xerox-copied version, ring bound in a Snoopy Dog file, which I am not sure I bought because it was cheap, or whether I was really that fond of Snoopy in my early twenties. I always thought I was rather a Garfield fan. That it happened to be Snoopy, is actually quite apt, in a way. Colin Rae recounts the episode of a little dog that had accompanied the Pretoria Commando during the 1894-campaign against the Hananwa of Mmalebôhô, got its head stuck in a kettle, was rescued by Rae - who else? - and then got the name Malaboch-in-a-Kettle. There is also a globe on my Snoopy file, which I only noticed again after years the other day. If I want to be poetic, or just downright superstitious about it, I might suggest that this was a prelude to the "transnational turn" (some) historical writing would be taking in the early twenty-first century, probably in response to the globalisation talk in so many related disciplines. In accordance with the prophecy of Snoopy, I was destined to find it attractive (it is one way to critique our profession's obsession with nations and nationalisms, not so?).